2016
DOI: 10.1007/s10903-016-0347-9
|View full text |Cite
|
Sign up to set email alerts
|

Morbidity, Self-Perceived Health and Mortality Among non-Western Immigrants and Their Descendants in Denmark in a Life Phase Perspective

Abstract: To enable preventive policies to address health inequity across ethnic groups, this review overviews the current knowledge on morbidity, self-perceived health and mortality among non-Western immigrants and their descendants in Denmark. A systematic search in PUBMED, SCOPUS, Embase and Cochrane as well as in national databases was undertaken. The final number of publications included was 45. Adult immigrants had higher morbidity, but lower mortality compared to ethnic Danes. Immigrant children had higher mortal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
32
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(41 citation statements)
references
References 47 publications
5
32
0
1
Order By: Relevance
“…Our findings are consistent with the many prior studies that have documented the close and potentially causal relationships of both sleep duration and ethnicity with a range of morbidities, [44][45][46] including cardio-metabolic outcomes, [47][48][49][50] hypertension, 51,52 stroke, 53,54 and depression. 55,56 Our findings and those of prior studies highlight the potential clinical impact of ethnicity-driven short and long sleep duration.…”
Section: Comparison To Previous Studiessupporting
confidence: 91%
“…Our findings are consistent with the many prior studies that have documented the close and potentially causal relationships of both sleep duration and ethnicity with a range of morbidities, [44][45][46] including cardio-metabolic outcomes, [47][48][49][50] hypertension, 51,52 stroke, 53,54 and depression. 55,56 Our findings and those of prior studies highlight the potential clinical impact of ethnicity-driven short and long sleep duration.…”
Section: Comparison To Previous Studiessupporting
confidence: 91%
“…The present thesis findings showed that the three patient groups were no exception and to have had challenges with living with T2DM in one way or another. Similar with former findings on self-perceived health [244,245], the findings in the quantitative studies showed that onethird of the Emirati and the Pakistani women reported having "poor" or "very poor" overall health. For the Kurdish participants, who expressed their experiences with T2DM management during focus group discussions, living with T2DM was described as stressful.…”
Section: Lifestyle Managementsupporting
confidence: 87%
“…The study's most important result -a statistically significant (p<.01) excess mortality among second-generation North African-origin adult males -is based on only 22 deaths in the ELM. Even though this result is consistent with other European studies (Scott and Timaeus 2013;De Grande et al 2014;Manhica et al 2015;Vandenheede et al 2015;Wallace 2016;Jervelund et al 2017), our study calls for replication in the French context. However, we are not aware of any alternative source of mortality data in France with variables allowing the proper identification of second-generation immigrants.…”
Section: Discussionsupporting
confidence: 92%
“…In proportionate terms, second-generation immigrants represented 6.0% of the total EU population in 2014, up from 5.2% in 2008 (Agafiţei and Ivan 2017). Although research is sparse, second-generation status has been identified in previous studies as an important source of health disparities in EU countries, with important disadvantages in mortality outcomes for certain second-generation subgroups, especially those of non-EU origin (Harding and Balarajan 1996;Razum et al 1998;Tarnutzer, Bopp, and Grp 2012;Scott and Timaeus 2013;De Grande et al 2014;Manhica et al 2015;Vandenheede et al 2015;Wallace 2016;Jervelund et al 2017). Explanations for these mortality disadvantages include lower socioeconomic status, detrimental health behaviors, and chronic stress arising from perceived discrimination (Scott and Timaeus 2013;De Grande et al 2014;Manhica et al 2015;Vandenheede et al 2015;Wallace 2016;Jervelund et al 2017).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation